Individual Variations in the Mastery of Discourse Connectives from Teenage Years to Adulthood. Issue 2 (20th February 2022) - Tskhovrebova, Ekaterina; Zufferey, Sandrine; Gygax, Pascal
Abstract: Many connectives, such as therefore and however, are used very frequently in the written modality. Their acquisition thus represents an important milestone in developing written language competences. In this article, we assess the development of competence with such connectives by native French speakers in a sentence‐level insertion task ( N = 307, aged 12 to 64) and a text‐level insertion task ( N = 172, aged 13 to 71). Our results indicate that, despite a general progression in the level of competence with age, the academic level of participants is a strong predictor of competence within each age group, even during adulthood. In addition, from the age of 12, competence is related to the frequency of connectives in naturalistic data, with frequent connectives systematically mastered better than less frequent ones. Finally, in all age groups, the use and understanding of connectives is more challenging when sentences to complete are embedded within a richer context than when presented alone. Abstract :